Odpowiedzi

Najlepsza Odpowiedź!
2009-11-18T16:37:55+01:00
1
x²-25=x²+9-6x
x²-x²+6x=9+25
6x=34/:6
x=3/17

2
4a²+1-4a=4a²-1
4a²-4a²-4a=-1-1
4a=-2/:4
x=-1/2

3
9x²-4-9+x²+1+2x=10x²-10+2x
4
8x-4x²+12=-(4x²+36)
8x-4x²+12=-4x²-36
8x-4x²=4x²=-36-12
8x=-48/:8
x=-6

akurat z tego mam sprawdzian i se powtorzyłam:]
2009-11-18T16:40:28+01:00
(x-5)(x+5)=(x-3)²
x²-25=x²-6x+9/:x²
-25=-6x+9/-9
-34=-6x
x=5.66

(2a-1)²=(2a+1)(2a-1)
4a²-4a+1=4a²-1/:4a²
-4a+1=-1
-4a=-2
a=0.5

(3x+2)(3x-2)-9(x+1)²=9x²-4-9x²-18x-1=-4-18x-1=-18x-3

4x(2-x)+12=-(2x+6)(2x-6)
8x-4x²+12=-4x²+36/+4x²
8x+12=36/-12
8x=24
x=3

2009-11-18T17:04:49+01:00
1. x²-25=x²-6x+9
6x=25+9
6x=34
x= 34/9 = 17/3

2. 4a²-4a+1 = 4a²-1
-4a=-2
a= 1/2

3. 9x²-4-9(x²+2x-1) = 9x²-4-9x²-18x-9 = -18x-13


4. 4x(2-x)+12 = -(2x+6)(2x-6)
8x-4x²+12=-(4x²-36)
8x-4x²+12=-4x²+36
8x=24
x=3